Danger to the Old Lady of Threadneedle Street? The Bank Restriction Act and the regime shift to paper money, 1797-1821 - Patrick K. O'Brien; Nuno Palma (European Historical Economics Society (EHES), 2016)
The Bank Restriction Act of 1797 suspended the convertibility of the Bank of England's notes into gold. The current historical consensus is that the suspension was a result of the state's need to finance the war, France's remonetization, a loss of confidence in the English country banks, and a run on the Bank of England's reserves following a landing of French troops in Wales. We argue that while these factors help us understand the timing of the Restriction period, they cannot explain its success. We deploy new long-term data which leads us to a complementary explanation: the policy succeeded thanks to the reputation of the Bank of England, achieved through a century of prudential collaboration between the Bank and the Treasury.
Keywords: N13; N23; N43; 330; Bank of England; financial revolution; fiat money; money supply; monetary policy commitment; reputation; and time-consistency; regime shift; financial sector growth